Spatial Disparities in Economic Development: The Role of Industrial Agglomeration, Public Investment, and Transportation Networks in Indonesia - Haryono Haryono (West Science Journal Economic and Entrepreneurship, 2025)
This study explores the spatial disparities in economic development across Indonesia, with a focus on the role of industrial agglomeration, public investment, and transportation networks. Despite the country’s overall economic growth, significant regional inequalities persist, particularly between Java and Bali, and the outer islands such as Papua and Maluku. Using a normative qualitative approach, this research examines the factors that contribute to these disparities. Industrial agglomeration is found to be a key driver of regional growth, with clustering of industries fostering innovation, job creation, and higher productivity. Public investment in infrastructure, education, and healthcare plays a critical role in mitigating these disparities, but its uneven distribution across regions exacerbates inequality. Transportation networks are essential for reducing transaction costs and facilitating economic integration, yet many remote areas still suffer from poor infrastructure, hindering their economic potential. The study concludes with policy recommendations to promote industrial development in underdeveloped regions, increase public investment, and enhance transportation networks to foster more balanced economic growth across Indonesia.